Determinasi Pakta AUKUS terhadap Keamanan Asia Tenggara - Adrianus L Wene (Kajian Asia Pasifik, 2021)
This paper is intended to analyze the determinations of the AUKUS Pact on the security of the Southeast Asian region. With this aim, the focus of the analysis will lead to the attitude or foreign policy of the countries of the Southeast Asian region and ASEAN's attitude towards the determination made by the AUKUS Pact towards the ASEAN Economic Community. The constellation of international relations in the Indo Pacific shows the struggle of two great powers, namely the United States and China. China's ambition to become a hegemonic regional power is manifested in economic maneuvers through the BRI and political maneuvers through the nine dash line claim in the South China Sea. This offensive Chinese activity poses a threat to the United States. As a reaction to China's maneuvers, the AUKUS Pact promises a balance of power as well as the potential to intensify Asia-Pacific security stability. The excesses of the constellation between the United States and China places Southeast Asian countries in a dilemma, including ASEAN which must be able to take on a role to accommodate common interests in Southeast Asia. This paper uses a historical perspective with the balance of threat theory from Stephen Walt. The findings from the paper are, first, the implications of the AUKUS Pact depend on the attitude of ASEAN member countries with two consequent models, namely creating security stability in the Southeast Asian region or causing security and peace instability; second, differences of opinion among ASEAN member countries emphasize ASEAN's inability to manage conflicts and all potential conflicts that threaten its regional security; third, the choice of balancing, bandwagoning or maintaining balance in different degrees between the United States and China is a rational choice for ASEAN member countries. The existence of the AUKUS Pact requires Southeast Asian countries to continuously develop their security mechanisms and strategies to address any potential that may occur in the future. Keywords: AUKUS Pact, China, United States of America, ASEAN, Balance of threat